2001
DOI: 10.1200/jco.2001.19.2.488
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Duration of Preoperative Therapy in Unilateral and Nonmetastatic Wilms’ Tumor in Children Older Than 6 Months: Results of the Ninth International Society of Pediatric Oncology Wilms’ Tumor Trial and Study

Abstract: The 4-week schedule pre-nephrectomy chemotherapy regimen should be considered the standard treatment. Clinical trials should continue to improve the cure rate of high-risk patients and the quality of life of children with a more favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
163
4
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(188 citation statements)
references
References 19 publications
14
163
4
3
Order By: Relevance
“…17 All other countries continued the well established SIOP approach of starting preoperative chemotherapy on the basis of clinical and imaging characteristics consistent with a diagnosis of Wilms' tumour, combined with measuring urinary catecholamines to exclude neuroblastoma, and reserving biopsy for cases with diagnostic dilemma. 2,18,19 Three-dimensional tumour volume was recorded at diagnosis and after completion of preoperative chemotherapy, according to whichever imaging method had been applied (ultrasonography, CT scan, or MRI scan). The calculated volume showed close correlation between methods (appendix).…”
Section: Methodsmentioning
confidence: 99%
“…17 All other countries continued the well established SIOP approach of starting preoperative chemotherapy on the basis of clinical and imaging characteristics consistent with a diagnosis of Wilms' tumour, combined with measuring urinary catecholamines to exclude neuroblastoma, and reserving biopsy for cases with diagnostic dilemma. 2,18,19 Three-dimensional tumour volume was recorded at diagnosis and after completion of preoperative chemotherapy, according to whichever imaging method had been applied (ultrasonography, CT scan, or MRI scan). The calculated volume showed close correlation between methods (appendix).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately two-thirds of patients with Wilms tumour now receive chemotherapy consisting of only two drugs, actinomycin D and vin cristine 11 . Other patients, including those with metastatic disease and high-risk histological subtypes, are believed to benefit from doxorubicin [12][13][14][15][16] . Moreover, as inno vative techniques emerge, surgical and radiotherapeutic procedures are improving.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Similar to the SIOP−2001 protocol, the UMBRELLA protocol continues to recommend preoperative actinomycin D and vincristine for patients newly diagnosed with Wilms tumour aged ≥6 months, based on results of previous SIOP trials that showed tumour downstaging using this regimen 2,6,8,9,14,17 . This benefit was also independently observed in the randomized, controlled UKW3 trial conducted by the UK Children's Cancer and Leukaemia Group (UKCCLG, previously known as the UK Children's Cancer Study Group) 18 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Children with a Wilms tumor were treated with preoperative chemotherapy, followed by a nephrectomy, systemic chemotherapy and when necessary with local radiation therapy, according to SIOP protocols 9 and 93-01 (D 'Angio, 1983;Tournade et al, 2001). Children with a Wilms tumor did not receive CNS-directed treatment.…”
Section: Research Participants and Treatment Protocolsmentioning
confidence: 99%